1978
DOI: 10.1007/bf01906751
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial amino acid metabolism in patients with chronic ischemic heart disease

Abstract: In nine patients with ischemic heart disease the authors investigated the arterio-coronary venous difference of free amino acids in serum at rest and during pacing. At rest aspartate was the only amino acid with a marked positive arterio-coronary venous difference. At the peak of pacing, in addition to aspartate, there is a significant positive arterio-coronary venous difference in glutamate, leucine and isoleucine and a significantly negative difference in cystine-cysteine and glutamine with asparagine. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…It is possible that, relative to the concen tration of amino acids in the perfusate (4 mM), the intracellular concentration of Asp became critically low during ischemia and was supplemented by the exogenously added Asp. In this regard, Brodan et al [1] observed that Asp was the only amino acid which the myocardium extracted to a signifi cantly greater extent during pacing-induced angina in patients with coronary heart dis ease. Also, Kao et al [5] reported that, in the isolated perfused rat heart, anoxia and isch emia caused approximately 75 and 35% de clines, respectively, in intracellular Asp con centrations, whereas no changes in Glu con centrations occurred.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, relative to the concen tration of amino acids in the perfusate (4 mM), the intracellular concentration of Asp became critically low during ischemia and was supplemented by the exogenously added Asp. In this regard, Brodan et al [1] observed that Asp was the only amino acid which the myocardium extracted to a signifi cantly greater extent during pacing-induced angina in patients with coronary heart dis ease. Also, Kao et al [5] reported that, in the isolated perfused rat heart, anoxia and isch emia caused approximately 75 and 35% de clines, respectively, in intracellular Asp con centrations, whereas no changes in Glu con centrations occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to glutamine, the use in the current study of a recently validated method for glutamine analysis (30) may contribute to the difference of results. It is worth noting that although the chromatographic procedure used in their study limited the resolution of glutamine, Brodan et al (11) reported that a combination of glutamine and asparagine was released by the ischemic human heart. These same authors observed uptake of leucine and isoleucine by human myocardium during pacing stress.…”
Section: Discussionmentioning
confidence: 99%
“…Brodan et al markedly observed a positive myocardial uptake of only aspartate at rest, an uptake of glutamate, leucine, and isoleucine, and the release of cystine-cysteine, glutamine, and asparagine during pacing in 9 patients with ischemic heart disease [30].…”
Section: Ia Glutamate/glutaminementioning
confidence: 99%